PRINCIPAL METHODS OF PREVENTION CORRUPTION AND FRAUD IN PUBLIC PROCUREMENT - Corina BOLOȘ; Lorant HERCZEG (Oradea Journal of Business and Economics)
In this article, we will analyze the mechanisms for combating corruption and fraud in Romania, taking into account the assessment of best practices, including operational capacities, efficiency of integrity mechanisms, control and sanctions. The phenomena of corruption and fraud in public procurement in Romania as well as the existence of these phenomena in more developed countries. The analysis was based on general literature on the phenomena of fraud and corruption, including the legal framework regulating these phenomena, taking into account the assessment of best practices, including operational capacities, effectiveness of integrity, control and sanction mechanisms. Bribery in public procurement is “embedded” in a general system of corruptible behaviors covering all categories of business, public and private. This report therefore attempts to provide – in part two – an assessment of the risks of corruption in public procurement. EU, World Bank and Transparency International data and reports have been taken for documentation. The main warning indicators can be listed as follows: bribery and illegal commissions; conflicts of interest; bid rigging; bid rigging; fictitious companies; disclosure of bid information; unbalanced bidding; bid rigging; manipulation of the bidding procedure; unjustified single-source and differentiated procurement; rigged specifications; exclusion of qualified bidders; unnecessary procurement and procurement fraud in contract implementation. In Romania, the development of corruption and fraud phenomena in the field of public procurement has a negative impact on the absorption of European funds and their existence is due to the inefficiency of the control system in the field of public procurement, which does not ensure effective monitoring and has a negative influence on the budgets of public entities.